FERMENTASI RUMPUT LAUT Eucheuma cottonii OLEH Lactobacillus plantarum - Wandansari, Baiq Daraquthni (Chem Info Journal, 2013)
Eucheuma cottonii has been known contain nutrients such as proteins, lipids, carbohydrates, vitamin C, Î±-tocopherol, and minerals. Nutrient content of seaweed can be utilized as a medium for the growth of lactic acid bacteria (LAB). Fermented seaweed by LAB can be used as probiotic drinks for patients with lactose intolerance. Fermentation by LAB produces primary metabolites like lactic acid, CO2, acetaldehyde and hydrogen peroxide. This study aims to obtain characteristic data of fermented E. cottonii of West Lombok, NTB by Lactobacillus plantarum (texture, color, smell, taste and pH). Fermentation E. cottonii by L. plantarum performed by addition of 5% glucose and 5% inoculum, and then incubated at 37 Â° C for 72 hours. The results showed that the fermentation of E. cottonii by L. plantarum produce fermented seaweed with characteristics: yellow-green jelly, yogurt sour odor, has a sour taste and slightly bitter with a pH of 3.